Poetic of words in the work of Branko Miljković: Relationships between poetics and auto-poetics - Jeftimijević-Mihajlović Marija (Baština, 2010)
The author maintains that in literary critics, links between explicit and implicit poetic in the creativity of Branko Miljković, have been stated a long time ago. Miljković often wrote himself that essays he is writing 'had been conditioned more by the poetry which he is writing than by the one on which he is writing about'. Therefore a lot of critical-essayistic texts of his can be considered as self-poetics commentaries. For almost each component of his poetics expressed in the poetry, Miljković gave the explanation in essays, and in critical reports. Out of his essayistic texts, it is likely one 'poetics theory' to be derived, which largely explains poetics creation of Miljković himself. Furthermore, the author says that theoretic thought of words, poem and poetry, and the phenomenon of the poem itself origination, its internal modulation are to be basic postulates of his poetry, and his essays as well. The word took up a privileged place in his poetry. The following titles of poems are witnessing that: 'Far away Words', 'Non-told Words', 'Futility of Words', 'Arrangement of Words', 'Until the Words Last', 'Words Run Dry in the Sand'. Finally, the author stresses that besides in poetry, Miljkovic's theoretical consideration on words were specially explicated in essays 'Poet and Word', 'For the One Poetic Art', 'Partially Said Words Which Tell', in which his conceptualization of words as 'subject matter for creative project of the spirit' was thoroughly elaborated.